Kajian Yuridis Terhadap Pelaksanaan Reklamasi di Teluk Ambon Baguala - Hulandari, Putri; Laturette, Adonia Ivone; Angga, La Ode (Faculty of Law, Universitas Pattimura, 2021)
Introduction: In connection with the reclamation of the coast and sea in Ambon City, to be precise in the Bay of Ambon Baguala, the recalamation process of Ambon Bay has begun to be carried out, indicating changes in the environmental conditions of waters and fisheries in Ambon Bay.Purposes of the Research: To study and analyze the implementation of reclamation in the Bay of Ambon Baguala. Methods of the Research: This research is a type of normative legal research, namely legal research whose object of study includes statutory provisions and documentary legal materials..Results of the Research: The results showed that the implementation of the reclamation was very dangerous for the villages in Baguala District. One of the areas most threatened with